FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN ALAT KONTRASEPSI SUNTIK PADA IBU DI BPM TIARMIN BR SITORUS. AMD.KEB DI DUSUN GARUT DESA BELUTU KECAMATAN KANDIS KABUPATEN SIAK - Debby Pratiwi; Ramadhani Syafitri Nst (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Family planning is an attempt to plan the number and distance of pregnancies using hormonal contraceptives. In Indonesia, injectable hormonal contraceptives are increasingly being used because of effective, practical,cheap and safe. This study aims to determine the associated factors with the choice of injection contraceptives for mothers at BPM Tiarmin Br Sitorus.Amd.Keb in Garut Hamlet, Belutu Subdistrict, Kandis District, Siak Regency in 2020. This study was an analytical survey with a cross sectional approach using Primary data is a questionnaire for the period March-April 2020. The sampling accidental sampling was 50 people. Data analysis in this study was univariate and bivariate analysis with the Chi Square test with α = 0.05. Based on the results of the chi-square statistical test, it was found that there was a significant relationship with the choice of injection contraceptives, namely the age factor, the value of ρ-value = 0.039, where the value of ρ-value <α = 0.05, the knowledge factor ρ-value = 0.027 where the value of ρ-value <α = 0.05, parity ρ-value = 0.018 where the value of ρ-value <α = 0.05, and husband’s support ρ-value = 0.062 where the value of ρvalue <α = 0.05. Based on the results of this study, it is suggested for BPM Tiarmin Br.Sitorus Amd. Keb is expected to be used as input in order to improve services, especially services in providing information about injection contraceptives